Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Smartphone Nokia Di Kota Denpasar - Adi Putra, I Putu Agus Purnama; Santika, I Wayan (E-Jurnal Manajemen, 2013)
This study of the effect of the Marketing Mix Decision Against Nokia Smartphone purchases in Denpasar. The purpose of this study was to determine the effect of simultaneous marketing mix Nokia Smartphone purchase decisions in Denpasar, to determine the effect of the marketing mix partially on Nokia Smartphone purchase decisions in Denpasar, and to determine which variables are the dominant influence on purchasing decisions in the Nokia Smartphone Denpasar city. The sample used in this study were 100 respondents to the purposive sampling technique. Data were analyzed using multiple linear regression analysis. Results of this study found that the marketing mix consists of product, price, promotion, and distribution simultaneously influence the purchasing decisions Smartphone Nokia in Denpasar. Partially, product, price, promotion, and distribution of positive and significant impact on purchasing decisions Smartphone Nokia in Denpasar. In this study, the price is variable dominant influence. It can be concluded that the marketing mix affect the purchase of Nokia Smartphone purchase decision in Denpasar.   Keywords : marketing mix, purchasing decisions, Smartphone